2018
DOI: 10.1371/journal.pone.0195365
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of maternal depressive symptoms during pregnancy and the first 12 months postpartum and child externalizing and internalizing behavior at three years

Abstract: BackgroundMost evidence of the association between maternal depression and children’s development is limited by being cross-sectional. To date, few studies have modelled trajectories of maternal depressive symptoms from pregnancy through the early postpartum years and examined their association with social emotional and behavior functioning in preschool children. The objectives of this study were to: 1) identify distinct groups of women defined by their trajectories of depressive symptoms across four time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
116
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 42 publications
16
116
1
8
Order By: Relevance
“…The variables that differed between the two clusters were all related to mental health problems, in that the women either had a history of mental illness, ongoing depressive symptoms or anxiety. Co-morbidity is common in women with fear of birth [33] and women might need treatment for their mental problems, as mental health problems could affect the health of both mother and baby [34], as well as prenatal attachment [35], for a long period after birth [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…The variables that differed between the two clusters were all related to mental health problems, in that the women either had a history of mental illness, ongoing depressive symptoms or anxiety. Co-morbidity is common in women with fear of birth [33] and women might need treatment for their mental problems, as mental health problems could affect the health of both mother and baby [34], as well as prenatal attachment [35], for a long period after birth [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…2 Department of Obestetrics, the Third Xiangya Hospital of Central South University,Changsha, China. 3 Department of Gynecology, the Third Xiangya Hospital of Central South University, Changsha, China. 4 Department of Psychiatry, the Third Xiangya Hospital of Central South University, Changsha, China.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Antenatal depression which can occur in any time during pregnancy, has been considered as a major public health problem. The consequences of antenatal depression may be severe and far-reaching, negatively affecting the mother and infant [1,2], including the increased risk of perinatal complications, adverse perinatal outcomes [3], and adverse effects on the development of infant cognition, behavior, emotion and intellectual [4].Evidence has shown that 50% postpartum depression begins at antenatal period [5], and antenatal depression is the most effective predictive factor for postpartum depression [6]. However, due to some physiological symptoms of pregnancy are overlapped with the antenatal depressive symptoms, it is difficult to well recognize the antenatal depressive symptoms [7].…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal depression (depression during pregnancy and postpartum period) particularly has a negative influence on infant and child development. 142,143 Various studies have shown that children born to women experiencing perinatal depression are at a higher risk for experiencing adverse behavioral and developmental outcomes including preterm birth, 144 externalizing and internalizing behaviors, 145,146 poor growth, 147 and reduced cognitive functioning. 148 Fathers are also at risk for experiencing perinatal depression, 149 though research on fathers' depression status during this time period is scarce 150,151 and its effect on child outcomes is unclear.…”
Section: Parental Depressionmentioning
confidence: 99%